Local content requirements in the petroleum sector in Tanzania: A thorny road from inception to implementation?. Issue 2 (April 2017) - Kinyondo, Abel; Villanger, Espen
Highlights: The large natural gas discoveries in Tanzania has triggered substantial economic and political activities concerning the management of the resources. We find that most stakeholders, both domestic and foreign, are in principle supportive of local content (LC) requirements to ensure Tanzanians benefit from the extraction. Nevertheless, there are strong concerns that the proposed LC policies would exacerbate corruption and patronage. Despite a relatively informed and competent segment of stakeholders that provide useful perspectives to LC policy development, there has been no proper consultation process. Short deadlines and minimal outreach has curbed the debate in Tanzania and contributed to increased suspiciousness among stakeholders. We generally find a high degree of mistrust between the key agents in the LC sphere. Stakeholders accuse the government of monopolizing the LC policy development process, and fear that weak capacity, corruption and rent-seeking could jeopardize their implementation of the LC policies. Foreign companies are accused of exploiting the Tanzanian resources and stakeholders proposed strict non-negotiable requirements in order to ensure that benefits also would accrue to Tanzanians. All in all, the high degree of mistrust between key stakeholders, and the very difficult business climate arising from widespread corruption and patronage, could undermine the implementation of the LC policies in the country. Abstract: Tanzania has recently discovered huge offshore natural gas fields. This has led the Government to develop local content policies (LCPs) to increase job and business opportunities for nationals in the sector. We study the process behind the development of these policies and the positions of stakeholders. We find that although there is a positive view among domestic stakeholders of imposing such policies, there is much suspicion—to such a degree that it shapes their recommendations of which policies to include in the LCP. One reason is that the Government monopolized the policy development process and abstained from conducting a consultative process. Our findings suggest that future Tanzanian policy development should include in-depth consultations to maximize the decision maker's knowledge base, add to the transparency of the process and manage expectations. This would also contribute to effective implementation and lessen tensions, conflicts and suspicion among stakeholders.